Vestibular Nerve Atrophy After Vestibular Neuritis – Results from a Prospective High-Resolution MRI Study - Freund, Wolfgang; Weber, Frank; Schneider, Daniel; Mayer, Ulrich; Scheithauer, Marc; Beer, Meinrad (RöFo : Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebende Verfahren, 2020)
Abstract Purpose Sudden unilateral peripheral vestibular deficit is mostly termed vestibular neuritis (VN), even if its cause or the exact location of the lesion remains unclear. Thus, therapy is mostly symptomatic. We aimed to prove if there is peripheral atrophy after VN with persistent canal paresis. Methods After approval by the ethics committee and according to the declaration of Helsinki and with informed consent, ten patients with persistent canal paresis after VN and ten age-matched healthy controls were included. High-resolution measurement (in-plane resolution 0.2 mm) of the internal auditory canal (IAC) using a 3 D CISS sequence at 3 Tesla was performed. The course of the pertaining nerves was reconstructed in the 3 D dataset and the measurement was performed at 60 % of the length of the IAC. The cross-sectional areas of the superior (SVN) and inferior vestibular nerve (IVN) were taken independently by two blinded readers. Results The interrater difference regarding the area was 22 %. We found significant atrophy of the SVN with a 24 % smaller area (p = 0.026) and found a smaller ratio of SVN/IVN on the symptomatic side (p = 0.017). Concerning single subject data, only 5 patients showed extensive atrophy of the NVS, while 5 patients did not. The time since symptom onset did not significantly influence the atrophy. Conclusion MRI measuring of the area of the NVS after VN could detect atrophy after VN. However, only 5 patients exhibited marked atrophy, while the other 5 patients did not. With the background of stringent inclusion criteria (more than 6 months of symptom duration and proven persistent canal paresis), one has to wonder if there might be different etiologies behind the apparently identical symptoms. Key Points: